Barbed and conventional sutures in spinal surgery patients: an economic and clinical outcomes comparison. (1st May 2020) - Johnston, Stephen S; Chen, Brian Po-Han; Tommaselli, Giovanni A; Jain, Simran; Pracyk, John B
Abstract : Objective: To compare economic and clinical outcomes of barbed sutures versus conventional sutures alone in wound closure for patients undergoing spinal surgery. Method: A retrospective study using the Premier Healthcare Database. The database was searched for patients who underwent elective inpatient spinal surgery (fusion or laminectomy) for a spinal disorder between 1 January 2014 and 30 June 2018 (first=index admission). Using billing records for medical supplies used during the index admission, patients were classified into mutually-exclusive groups: patients with any use of STRATAFIX (Ethicon, US) knotless tissue control devices (barbed sutures group); or patients with use of conventional sutures alone (conventional sutures group). Outcomes included the index admission's length of stay, total and subcategories of hospital costs, non-home discharge, operating room time (ORT, minutes), wound complications and readmissions within ≤90 days. Propensity score matching and generalised estimating equations were used to compare outcomes between the study groups. Results: After matching, 3705 patients were allocated to each group (mean age=61.5 years [standard deviation, SD±12.9]; 54% were females). Compared with the conventional suture group, the barbed suture group had significantly lower mean ORT (239±117 minutes, versus 263±79 minutes conventional sutures, p=0.015). Operating room costs were also siginificantly lower in the barbed suture group ($6673±$3976 versus $7100±$2700 conventional sutures, p=0.020). Differences were statistically insignificant for other outcomes (all p>0.05). Subanalysis of patients undergoing fusions of ≥2 vertebral joints yielded consistent results. Conclusion: In this study, wound closure incorporating barbed sutures was associated with lower ORT and operating room costs, with no significant difference in wound complications or readmissions, when compared with conventional sutures alone.